1996
DOI: 10.1177/00220345960750010501
|View full text |Cite
|
Sign up to set email alerts
|

Cariogenicity Depends More on Diet than the Prevailing Mutans Streptococcal Species

Abstract: Abstract. This review aims to compare the occurrence and distribution of mutans streptococci in Africa, Europe, and North America and in addition will try to offer explanations for existing relationships among salivary mutans streptococci counts, dietary patterns, and dental caries. The literature reveals that salivary mutans streptococci counts in child populations of the three continents are comparable. The distribution of mutans streptococci species, with a predominance of S. mutans followed by S. sobrimis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
55
1
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 73 publications
7
55
1
1
Order By: Relevance
“…However, several studies have shown that normal oral hygiene procedure, and even professional tooth cleaning seem to have minor effects on the numbers of mutans streptoococci in the oral cavity. 29 There are reasons to believe that the intake of sugar, Intake of sweet foods in women B Barkeling et al especially when frequent, favours the prevalence of mutans streptococci in saliva and dental plaque. 29 One limitation of this study is that the questionnaire does not cover the total dietary intake.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have shown that normal oral hygiene procedure, and even professional tooth cleaning seem to have minor effects on the numbers of mutans streptoococci in the oral cavity. 29 There are reasons to believe that the intake of sugar, Intake of sweet foods in women B Barkeling et al especially when frequent, favours the prevalence of mutans streptococci in saliva and dental plaque. 29 One limitation of this study is that the questionnaire does not cover the total dietary intake.…”
Section: Discussionmentioning
confidence: 99%
“…Immediately after samples were collected, saliva was homogenized for 30 seconds, diluted 1:1000 (v/v) in sterile distilled water and an aliquot of 50 μL sowed on selective Trypticase-yeast-cysteinesucrose-bacitracin agar plates (TYCSB) (Merck, Darmstadt, Germany) modified by addition of 20% sucrose (w/v) (Merck, Darmstadt, Germany) for S. mutans, as described (13) . Plates were incubated at 37ºC for 48 h in anaerobic jars (Gen Box Anaer; bioMérieux, Marcy-l'Etoile, France), followed by phenotypical colony identification, considering as S. mutans only those adherent, irregular and sugar grain-like colonies, as described elsewhere (21) .…”
Section: S Mutans Culture and Countsmentioning
confidence: 99%
“…High counts of Mutans streptococci (MS), Streptococcus mutans (S. mutans) and Streptococcus sobrinus, have been associated with higher prevalence of coronal caries in temporary and permanent dentitions (3)(4)(5)(6)(7) and also root caries (8)(9)(10)(11) . In spite of the widely acknowledged association between increased levels of MS and higher caries experience, other studies have argued against this association (12,13) . Colonization and pathogenicity of these facultative Gram(+) cocci derive from their capacity to synthesize extracellular polysaccharides (14) .…”
Section: Introductionmentioning
confidence: 99%
“…Alaluusua et al (1996) suggested that some strains of S. mutans might be able to colonize the host and induce dental caries better than other strains. Alternatively, dietary patterns of the host may be an important factor, since a high salivary mutans streptococci count does not necessarily exert a cariogenic challenge (van Palenstein Helderman et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Alaluusua et al (1996) suggested that some strains of S. mutans might be able to colonize the host and induce dental caries better than other strains. Alternatively, dietary patterns of the host may be an important factor, since a high salivary mutans streptococci count does not necessarily exert a cariogenic challenge (van Palenstein Helderman et al, 1996).Numerous factors affect the equilibrium among oral populations of micro-organisms, and several inhibitory substances have been identified, including mutacins (Fukushima et al, 1985;Caufield et al, 1985;Delisle, 1976). Mutacins are peptide or protein antibiotics that are mainly bactericidal for other bacteria of the same or closely related species, as well as for other Gram-positive micro-organisms, and are likely to confer an ecological advantage in diverse bacterial communities such as the dental biofilm (Parrot et al, 1990; Balakrishnan et al, 2002).…”
mentioning
confidence: 99%